2015
DOI: 10.1002/masy.201400028
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific Anionic Polymerization of α‐(Hydroxymethyl)acrylate with Protective Group

Abstract: Summary: Anionic polymerizations of hydroxyl-protected α-(hydroxymethyl) acrylates were investigated. The methyl ester with methoxymethyl (1-MOM) and allyl (1-allyl) protecting groups were polymerized by isopropyl α-lithioisobutyrate (Li-iPrIB) in toluene at 78 °C, affording highly isotactic polymers. Similarly, the polymerization of ethyl ester (2-MOM) gave an isotactic polymer, while those of t-butyl (3-MOM) and isobutyl (4-MOM) ester did not form any polymeric products. The hydrolysis of poly(2-MOM) in aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…α‐(Alkoxymethyl)acrylate, acyclic analogues of DMDO, is known to undergo spontaneous termination in anionic polymerization via the elimination of the respective alkoxide anion to afford a polymer with terminal chain‐end of an α,β‐unsaturated ester [Scheme (a)] …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…α‐(Alkoxymethyl)acrylate, acyclic analogues of DMDO, is known to undergo spontaneous termination in anionic polymerization via the elimination of the respective alkoxide anion to afford a polymer with terminal chain‐end of an α,β‐unsaturated ester [Scheme (a)] …”
Section: Resultsmentioning
confidence: 99%
“…In the previous work, we have found that the acid‐hydrolysis of the polymer of a methoxymethyl acetal‐protected α‐ (hydroxymethyl)acrylate prepared by anionic polymerization caused a side reaction, that is, lactonization between the neighboring two units via ester exchange reaction . In contrast, P1 , the cyclic‐acetal protected poly[α‐(hydroxymethyl)acrylate], underwent clean deprotection to generate hydrophilic α‐hydroxymethyl groups together with carboxylic groups, indicating that the cyclic‐acetal protection is effective for the protection of α‐(hydroxymethyl)acrylate derivatives.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have been interested in the polymerization behavior of α‐substituted acrylates and recently have found that α‐(halomethyl)acrylate and α‐(alkoxymethyl)acrylate functioned as an efficient terminator in stereospecific anionic polymerizations of methyl methacrylate (MMA); the poly(methyl methacrylate) (PMMA) living anion attacks the vinylidene group of the terminators, and the subsequent elimination of halogen atom or alkoxy group generates PMMA with α,β‐unsaturated ester moiety at the ω‐end. For example, the polymerization initiated by isopropyl α‐lithioisobutyrate (Li‐­ i PrIB) in the presence of ethylaluminum bis(2,6‐di‐ tert ‐butylphenoxide) [EtAl(ODBP) 2 ] could be terminated with ethyl α‐(chloromethyl)acrylate (ECMA) to afford highly syndiotactic ( st ‐) PMMA with ω‐functionality (termination efficiency: F ≈ 99%) .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have been interested in α‐substituted acrylates as functional monomers or functional terminating agents in anionic polymerization. As an extensive research in this line, the unique reactivity of MPhA has attracted our interest in designing new functional polymers with aromatic substituents directly attached to the polymer backbones.…”
Section: Introductionmentioning
confidence: 99%